Strategi Peningkatan Pendapatan Petani Desa Labbo Melalui Pengelolaan Keuangan Cerdas - Darmawati Darmawati; Andi Kusumawati; Kartini Kartini; Rahmawati HS; Muh. Reza Pehlevi Juanda; Andi Izzah Fadhilah Natsir; Indira Syakira Kirana Juanda (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
The Smart Financial Management Program in Labbo Village aimed to enhance farmers’ and BUMDes managers’ financial literacy through training in financial management, recordkeeping, reporting, and loan proposal preparation. Using participatory and learning-by-doing approaches, the program effectively improved participants’ understanding of basic accounting and financial practices. Results showed better transaction recording, monthly financial reporting, and access to formal credit institutions. The program strengthened transparency, accountability, and data-based financial culture. Labbo Village now serves as a model for sustainable rural financial literacy development.